(untitled) (Journal of Parents and Teachers, 2023)
Positive Discipline understands leadership as one hat helps team members feel that they belong and that they are significant. In this article we will see how organizations can achieve this and how they can develop leadership that builds relationships based on mutual respect and treats people with kindness and firmness at the same time.